The Unequal Impact of Natural Light on Crime - Emiliano Tealde (Global Labor Organization (GLO), 2020)
This paper studies the relationship between ambient light and criminal activity. A Becker-style crime model is developed where it is shown that in areas with less public lighting a sudden increase in ambient light produces a higher reduction in crime. The Daylight Saving Time, the natural experiment used, induces a sharp increase in natural light during crime-intense hours. Using geolocated data on crime and public lighting for the city of Montevideo in Uruguay, regression discontinuity estimates identify a strong and statistically significant decrease in robbery of 17-percent. The decrease is larger in poorly lit areas. Computing the level of public lighting at which DST has no effect on crime reduction, we identify the minimum level of public lighting that an area should target.
Keywords: K24; 330; DST; property crime; public lighting; heterogeneous effects